2020
DOI: 10.1038/s41427-020-0197-8
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of p–n conduction type by spinodal decomposition in Zn-Sb-Bi phase-change alloys

Abstract: Phase-change films with multiple resistance levels are promising for increasing the storage density in phase-change memory technology. Diffusion-dominated Zn 2 Sb 3 films undergo transitions across three states, from high through intermediate to low resistance, upon annealing. The properties of the Zn 2 Sb 3 material can be further optimized by doping with Bi. Based on scanning transmission electron microscopy combined with electrical transport measurements, at a particular Bi concentration, the conduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…PCMs usually lie in the pseudobinary tie-line between GeTe and Sb 2 Te 3 in the Ge-Sb-Te (GST) [55,56] ternary phase diagram (Figure 2a). Besides the prototypical GST medium, other materials in this phase diagram such as doped Sb 2 Te [57] and pure [58] or alloyed [59,60] Sb were also frequently studied and showed excellent performance. The application of data storage exploits the fast and reversible transition between the amorphous and metastable crystalline phases of PCMs, e.g., crystallization by joule annealing or glass forming by melt-quenching (see the atomic models in Figure 2b and the memory switching operations in Figure 2c).…”
Section: Structure and Bonding Naturementioning
confidence: 99%
“…PCMs usually lie in the pseudobinary tie-line between GeTe and Sb 2 Te 3 in the Ge-Sb-Te (GST) [55,56] ternary phase diagram (Figure 2a). Besides the prototypical GST medium, other materials in this phase diagram such as doped Sb 2 Te [57] and pure [58] or alloyed [59,60] Sb were also frequently studied and showed excellent performance. The application of data storage exploits the fast and reversible transition between the amorphous and metastable crystalline phases of PCMs, e.g., crystallization by joule annealing or glass forming by melt-quenching (see the atomic models in Figure 2b and the memory switching operations in Figure 2c).…”
Section: Structure and Bonding Naturementioning
confidence: 99%
“…Sb2Te3 films deposited at 364 ºC demonstrates the highest power factor due to high Seebeck coefficient and moderate electrical conductivity. An average power factor over 15 µW/cm•K 2 in the temperature range from 200 K to 400 K is obtained which is competitive among some of the recent thin film works [46][47][48][49] . This demonstrates the capability of our SSP-based CVD in controlling and optimizing the thermoelectric properties.…”
Section: Sb2te3 Thin Filmmentioning
confidence: 80%
“…[4][5][6][7][8][9][10] Particularly, the recent literature survey of the last decade reveals that zinc is one of the building elements of phase change materials (PCMs) for use in phase change optical memory. [11][12][13][14][15][16][17] These features compelled various research groups to utilize Zn as a modier for preparing multicomponent (binary and ternary) ChGs. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Mehta et al 18 compared the effective values of thermal diffusivity and corresponding thermal conductivity of binary Se 90 Zn 10 and Te 90 Zn 10 alloys and found that both parameters are lower for Se 90 Zn 10 alloy as compared to Te 90 Zn 10 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…4–10 Particularly, the recent literature survey of the last decade reveals that zinc is one of the building elements of phase change materials (PCMs) for use in phase change optical memory. 11–17 These features compelled various research groups to utilize Zn as a modifier for preparing multicomponent (binary and ternary) ChGs. 18–35…”
Section: Introductionmentioning
confidence: 99%